Preliminary Study of Kisspeptin mRNA-expressing Neurons at POA and ARC in Hypothalamus of Beef Cattle - Songphasuk, Techaphon; Wannapong, Napasaporn; Thanantong, Narut; Sajapitak, Somchai (Journal of Mahanakorn Veterinary Medicine, 2021)
At present, there are more studies about the Kiss1 gene in the hypothalamus that produce the kisspeptin proteins and have an important role in the reproductive system. The previous research found the location of expression of Kiss1 gene is different about each species and sex. But, there are a few studies about the location of Kiss1 gene in cattle. Therefore, the objective of this study was a preliminary study to localize Kiss1 mRNA expression in the area of POA and ARC nucleus in the hypothalamus. By used a chromogenic in situ hybridization staining for Kiss1 gene in the cattle brain revealed that kisspeptin neuronal populations were localized in the POA and ARC of the hypothalamus. This study used three cattle brains including one female, one castrated male, and one intact male. And the result showed that the expression of kisspeptin mRNA-positive cells in the POA was about 64 cells that only expressed in female cattle. And the expression of kisspeptin mRNA-positive cells in the ARC were 1,127, 1,064, and 373 in female, castrated male, and intact male cattle respectively. However, this study is only to specify the location of kisspeptin mRNA in cattle brains, without considering the factors that may affect the expression of kisspeptin mRNA including, health status, stress-induced, management and age. Therefore, further studies are required for developing and applying to reproductive management in cattle.